1999
DOI: 10.1002/srin.199905607
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of the simultaneous desulfurization and dephosphorization processes of hot metal with CaO- and BaO-based slags bearing MnO

Abstract: The technical feasibility of the simultaneous desulfurization and dephosphorization process of hot metal with high basicity slags of the BaO‐BaF2 system is discussed from the thermodynamic point of view. The partition ratios as well as the degrees of removal of sulphur and phosphorus from the hot metal obtained after a single refining step with BaO‐saturated slags have been compared to those achieved when typical hot metal pretreatment slags of the system CaO‐CaF2‐SiO2 (double saturated with CaO and 3CaO•SiO2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Based on the reviews above, although there have been a number of studies on the dephosphorisation of Cr-containing hot metal, concerns related to high toxicity of Ba-containing slag [10], generation of toxic SiF 4 gas caused by a high concentration of CaF 2 [13] and low dephosphorisation ratio, have limited their application in actual production. In addition, most of the reports focused on the dephosphorisation of high-chromium hot metal and thus do not provide effective guidance for the dephosphorisation of hot metal containing moderate concentrations of chromium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the reviews above, although there have been a number of studies on the dephosphorisation of Cr-containing hot metal, concerns related to high toxicity of Ba-containing slag [10], generation of toxic SiF 4 gas caused by a high concentration of CaF 2 [13] and low dephosphorisation ratio, have limited their application in actual production. In addition, most of the reports focused on the dephosphorisation of high-chromium hot metal and thus do not provide effective guidance for the dephosphorisation of hot metal containing moderate concentrations of chromium.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al performed thermodynamic calculations and experiments for dephosphorisation of hot metal containing Cr and Ni at 1673 to 1684 K using CaO-based slag, resulting in a dephosphorisation ratio of 36% [9]. Cruz et al found a low (maximum 45%) dephosphorisation efficiency of hot metal using CaO-based slags bearing MnO, which is much lower than using BaO-based slags [10]. From these studies, it can be concluded that the dephosphorisation efficiency is relatively low and mostly lower than 60% for Cr-containing hot metal without the addition of high basicity BaO.…”
Section: Introductionmentioning
confidence: 99%